Multiculturalism in elementary school curricula in the Republic of Serbia and Hungary - Filipović, Aleksandra; Milovanović, Anđela (Norma, 2023)
Paper presents a comparative analysis of approaches to multiculturalism in the elementary school curricula of the Republic of Serbia and Hungary for grades one through four. The analysis aimed to examine multiculturalism within the prescribed curricula of these countries, how diversity and intercultural understanding are promoted, and the results show that both countries recognize the importance of understanding and respecting different cultures and identities while encouraging the development of empathy and tolerance among students. Through various content areas such as literature, arts, and music, the curricula of both countries tend to inspire students to appreciate cultural diversity and identities. Differences exist in emphasized elements, where the Hungarian curriculum leans more towards enhancing national Hungarian heritage, while the Serbian curriculum highlights cultural diversity both domestically and internationally. Based on an examination of approaches to multiculturalism in the elementary school curricula of the Republic of Serbia and Hungary, future research could delve deeper into the effectiveness of these programs in achieving multiculturalism goals, with a particular focus on the awareness and training of teachers for implementing these contents, recognized as an essential predictor in the literature for achieving multicultural education.
Keywords: multiculturalism; multicultural education; multicultural awareness; identity; curriculum